PERTANGGUNGJAWABAN PERDATA PT. WIJAYA KARYA TERHADAP SMKN 2 SAMARINDA TERKAIT KEGIATAN PEMBANGUNAN FLY OVER JL. AW. SYAHRANI (BERDASARKAN PERATURAN PEMERINTAH NO. 19 TAHUN 2005 TENTANG STANDAR NASIONAL PENDIDIKAN) - Rico Andreas (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACTEducation is learning the knowledge, skills, and habits of a group of people passed down from one generation to the next through teaching, training, or research. Education is often the case under the guidance of others, but also allows autodidact. Education must remain a top priority for the completeness of its facilities and infrastructure cultivated mainly for school. One important task of the school is to prepare students to be able to achieve optimal development. A student said to achieve optimal development if students can receive education and learning achievements appropriate to their talents, abilities and interests of its. Environment is one of the supporting factors that affect children's learning achievement. One environmental factor is the school environment. School as a formal educational institution that is very close to the views of the child activities are fun ways of teaching, curriculum, teacher relationships with students who are very close, students are adequate facilities, adequate facilities and infrastructure to support learning activities as well as the atmosphere of a school environment that is not crowded. All play an important role in the development of learning achievement of children.Keywords : Education , school environment, and infrastructure